MODEL PEMBELAJARAN BLENDED LEARNING (DARING DAN LURING) DALAM MATA PELAJARAN SKI KELAS XI DI MA ALMAARIF SINGOSARI - Dia Anggraini; Syamsu Madyan; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The blended learning model of islamic cultural history is a new challenge experienced by teachers and students at MA Almaarif Singosari during the pandemic. The focus of the research discusses the planning, implementation, and evaluation of online and offline learning in the history of Islamic culture. To achieve this goal, the researcher uses a qualitative approach based on phenomenology by using a case study type of research. The researcher found the results of the study included planning which consisted of making a learning implementation plan, preparing learning media, and preparing teaching materials, for the implementation it included the media used, time allocation, and teaching materials used, then for evaluation included learning evaluation by looking at the results of the study cognitive, affective, and psychomotor values consisting of student learning outcomes, student scores taken from the results of daily assignments, and test scores.